Mengembangkan Keterampilan Literasi Agama: Kontribusi Guru PAI dalam Pengenalan Al-Qur'an kepada Siswa Kelas I Sekolah Dasar: - Muryati, Muryati; Hariyanti, Hariyanti (Edu Berkah Khatulistiwa, 2024)
This article reviews the important role of Islamic Religious Education (PAI) teachers in developing religious literacy skills through teaching the Qur'an to first-grade elementary school students. By using innovative teaching methods, PAI teachers aim to create a learning environment that supports and develops reading, writing, and speaking skills about Islamic teachings. This article explains how PAI teachers play the role of agents of character formation and spirituality of children in the context of teaching the introduction of the Qur'an. Thus, this article provides insight into the efforts of PAI teachers to introduce the Qur'an from an early age, understand its meaning, and internalize the teachings contained in it. Introducing that the Qur'an is a provision for students' lives to become devout human beings. and developing religious literacy skills. Religious literacy needs to be introduced, taught, and habituated from an early age so that they can live in modern society today. So that students do not just know and carry out religious activities without knowing the purpose and purpose of the value being carried out. This article aims to find out (1) what are the contributions of PAI teachers in introducing the Qur'an to first-grade students. (2) What are the obstacles for PAI teachers in introducing the Qur'an to first-grade students? Type of research used. The method used in this study uses a qualitative research method, this research instrument uses observation, to check the validity of the data to get accurate results. From the results of this study, the researcher stated that PAI teachers are student learning resources, facilitators, managers, motivators, and evaluators. Therefore, the contribution of PAI teachers in introducing the Qur'an to first-grade students is very important.